Case report: A novel approach of closed-loop brain stimulation combined with robot gait training in post-stroke gait disturbance - Shima, Atsushi; Miyake, Tomoaki; Tanaka, Kazuki; Ogawa, Akari; Omae, Erika; Nagamori, Yui; Miyata, Yusuke; Ohata, Koji; Maki, Takakuni; Ono, Yumie; Mima, Tatsuya; Takahashi, Ryosuke; et al. (Frontiers in Human Neuroscience, 2023)
Most post-stroke patients have long-lasting gait disturbances that reduce their daily activities. They often show impaired hip and knee joint flexion and ankle dorsiflexion of the lower limbs during the swing phase of gait, which is controlled by the corticospinal tract from the primary motor cortex (M1). Recently, we reported that gait-synchronized closed-loop brain stimulation targeting swing phase-related activity in the affected M1 can improve gait function in post-stroke patients. Subsequently, a gait-training robot (Orthobot®) was developed that could assist lower-limb joint movements during the swing phase of gait. Therefore, we investigated whether gait-synchronized closed-loop brain stimulation combined with robot-assisted training targeting the swing phase could enhance the recovery of post-stroke gait disturbance. A 57-year-old female patient with chronic post-stroke hemiparesis underwent closed-loop brain stimulation combined with robot-assisted training for 10 min 2 years after left pons infarction. For closed-loop brain stimulation, we used transcranial oscillatory electrical current stimulation over the lesioned M1 foot area with 1.5 mA of DC offset and 0–3 mA of sine-wave formed currents triggered by the paretic heel contact to set the maximum current just before the swing phase (intervention A; two times repeated, A1 and A2). According to the N-of-1 study design, we also performed sham stimulation (intervention B) and control stimulation not targeting the swing phase (intervention C) combined with robot-assisted training in the order of A1-B-A2-C interventions. As a result, we found larger improvements in gait speed, the Timed Up and Go test result, and muscle strength after the A1 and A2 interventions than after the B and C interventions. After confirming the short-term effects, we performed an additional long-term intervention twice a week for 5 weeks, for a total of 10 sessions. Gait parameters also largely improved after long-term intervention. Gait-synchronized closed-loop brain stimulation combined with robot-assisted training targeting the swing phase of gait may promote the recovery of gait function in post-stroke patients. Further studies with a larger number of patients are necessary.